1986
DOI: 10.1126/science.3024321
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the DNA-Eco RI Endonuclease Recognition Complex at 3 Å Resolution

Abstract: The crystal structure of the complex between Eco RI endonuclease and the cognate oligonucleotide TCGCGAATTCGCG provides a detailed example of the structural basis of sequence-specific DNA-protein interactions. The structure was determined, to 3 A resolution, by the ISIR (iterative single isomorphous replacement) method with a platinum isomorphous derivative. The complex has twofold symmetry. Each subunit of the endonuclease is organized into an alpha/beta domain consisting a five-stranded beta sheet, alpha hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
317
0
1

Year Published

1991
1991
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 508 publications
(332 citation statements)
references
References 60 publications
14
317
0
1
Order By: Relevance
“…The predictions of Seeman et al were essentially confirmed in the first crystal structure of a protein-DNA complex, EcoRI endonuclease-DNA, in which some 12 hydrogen bonds formed between 6 amino acid residues and the six base pairs in the recognition site were implicated to contribute to recognition [20]. The "helix swap" experiments of Wharton and Ptashne [28,29] and mutational studies in a similar vein provide further support of the role FIG.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…The predictions of Seeman et al were essentially confirmed in the first crystal structure of a protein-DNA complex, EcoRI endonuclease-DNA, in which some 12 hydrogen bonds formed between 6 amino acid residues and the six base pairs in the recognition site were implicated to contribute to recognition [20]. The "helix swap" experiments of Wharton and Ptashne [28,29] and mutational studies in a similar vein provide further support of the role FIG.…”
Section: Introductionsupporting
confidence: 62%
“…1) is the focus of our current investigation. This complex is particularly propitious for study, since the structure of the binary complex and the uncomplexed DNA have been determined from crystallography [20][21][22], and extensive experiments on binding equilibria have been carried out [23]. We describe herein a detailed analysis of the binding free energy for the EcoRI DNA complex based on a thermocycle of seven steps, with the contributions to free energy for each step of the cycle delineated with regard to the current "toolchest" of techniques for making reasonable theoretical estimates.…”
Section: Introductionmentioning
confidence: 99%
“…The preliminary model of the endonuclease EcoRI (McClairen et al, 1986) contained several structural errors and misconnections. At distance limits of 3.00-3.75 A, all of the incorrect regions are identified as suspect (residues 20-50, 60-170, 208-233, 240-C-terminus), while all but 5% of the corrected structure (Kim et al, 1990) lies within the 95% confidence limit (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Attention has become focused on the problem of evaluating the correctness of protein structures since the recent discoveries of serious errors in a number of published structures (Ghosh et al, 1982;McClairen et al, 1986;Chapman et al, 1988;de Vos et al, 1988;Navia et al, 1989).…”
mentioning
confidence: 99%
“…EcoRI-DNA complex Recently, the structure of the EcoRI-DNA complex has been reinterpreted, although the essential features of the previous structure remain unaltered, but a detailed description of the structure is at present unavailable . In summary, the EcoRI-DNA complex has two-fold symmetry which is related to the symmetry of the recognition sequence (McClarin et al, 1986). The structure of the DNA in the complex is generally of B-form although there are three distinct areas where the DNA is kinked (McClarin et al, 1986 structural elements involved in specific DNA contacts are a parallel fl-sheet, a novel f-bridge structure and two a-helices from each monomer, their orientation such that their N-terminal ends are pointing in the direction of the DNA-phosphate backbone, allowing favourable helix dipole-phosphate interactions (McClarin et al, 1986;Kim et al, 1990).…”
Section: Zif268-dna Complexmentioning
confidence: 99%